(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main objective of the present paper is to report the process of development and Standardization of test of algebraic reasoning (TAR) for grade VIII school students. Content for the test development is selected from the NCERT text book and U.P Basic Shiksha Parishad board. Initially a multiple choice test of 68 items from VIII grade Mathematics syllabus was selected and designed on the selected topics in such a way to test the algebraic reasoning of the students in algebra. For trying out the preliminary draft of the test of algebraic reasoning, the test was administrated to a sample of 200 grade VIII students of Varanasi district. The difficulty value (DV) and discriminating power (DP) of the test items were determined by adopting Kelley’s (1939) method. On the basis of the DV and DP the preliminary draft of the test was modified. In total 32 items having difficulty value (DV) ranging from 0.20 to 0.75 and the items ranging from 0.40 and above as the discriminating power (DP) were retained for the final test.